Factors affecting intention to use learning management system among employees of Telekom Malaysia - Meor Ahmad Shahruzzaman, Meor Hashim (2022)
In this era, knowledge is the best way to strengthen organisational performance. Telekom Malaysia (TM) believes that knowledge is the key to success and has created a customised learning path for each employee. For these reasons, TM has implemented a new Learning Management System (LMS). However, records showed that the usage of the current LMS is very low, and the actual cause is still not apparent. This study focuses on identifying the factors affecting the learner’s intention to use LMS by incorporating the element of human factors. The Unified Theory of Acceptance and Use of Technology (UTAUT) was used to address the human factors perspective. UTAUT identifies performance and effort expectancy, social influence, and facilitating conditions as direct determinants of behavioural intention. Training construct was included in the model because of its importance in strengthening the learner’s intention and how it is thought to contribute to the organisation’s bottom line values. The research used a quantitative approach. The study’s first phase validated the construct measurement. A primary survey was then undertaken to test the study hypotheses and conceptual model. Structural equation modelling was used in particular, utilising 27 items in the questionnaire. Overall, the statistical findings showed that the results were fit for the data, with satisfactory nomological validity and reliability. This study reported significant relationships between social influence, facilitating condition, training and learner’s intention. However, performance expectancy and effort expectancy did not significantly correlate with the learner’s intention. This study recommends that organisations emphasise the need and preference of the end-user by including employees as primary stakeholders from the start of the LMS implementation stage. Additionally, management should also consider training as one of the main factors to improve LMS adoption.